Klasifikasi asal geografis kopi bubuk liberika tungkal Jambi dan Probolinggo menggunakan near-infrared spectroscopy (NIRS) dan principal component analysis (PCA) - Ikhsan Nurdziky; Anggoro Cahyo Sukartiko; Nafis Khuriyati (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Regional origin classification of Geographical Indication (GI) products is necessary for their authentication purpose. Among others, coffee is Indonesia's largest GI group, with Liberica being the least studied. This study aims to classify the geographical origin of dry- and honey-processed Liberica Tungkal Jambi ground coffee, which has been certified and dry-processed Liberica Probolinggo, which has the potential to be certified in the future. A total of 12 samples were tested using Near-Infrared Spectroscopy (NIRS). Spectrum data were analyzed using Principal Component Analysis (PCA) with various preprocessing spectral data, including Multiplicative Scatter Correction (MSC), Baseline, and Detrending. The results showed the ability of the combination of NIRS and PCA to classify three groups of coffee samples, namely: dry-processes Liberica Tungkal Jambi ground coffee, honey-processed Liberica Tungkal Jambi ground coffee, and dry-processed Liberica Probolinggo ground coffee, with the success rate ranged between 88 to 99%. Detrending was the most effective preprocessing for visualizing the classification. The result illustrates the great potential of near-infrared (NIR) spectroscopy in classifying the geographical origin of Liberica ground coffee.